PENGEMBANGAN APLIKASI PRACTICAL ERP UNTUK STARTUP KEMITRAAN USAHA PRODUKSI HIJAUAN PAKAN TERNAK - suprihadi suprihadi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
The Ministry of Education and Culture's 2022 Matching Fund Project is the implementation of a new business model canvas in the form of a practical ERP, which is specifically designed for specific production businesses from upstream to downstream businesses, namely startups in the Forage Production business. This project builds a collaboration ecosystem between Satya Wacana Christian University and CV. Cahaya Baru as a Partner, also aims to alleviate underprivileged families and restore the economy affected by the Covid-19 pandemic in Kadirejo Village, Semarang Regency. To involve the surrounding community, a partnership startup was formed, including Land Partners, and Production House Partners as Product Processing Units. There are 4 main stages in the methodology used, starting with identifying the conditions of the partners, Formulating and Analysis of System Development Needs, Application Development to Operational Assistance and Maintenance. One of the results is a startup application called eRumputTernak, developed using the prototype model method. This activity was supported by 28 MBKM program students. The Program Partners involve around 60 people, especially Pre-Prosperous families as Land Partners and workers in the 12 hectare Pakchong grass production business, from planting to harvesting. The Program Partners are also assisted with the procurement and training of production equipment, in the form of 1 unit of the Silage Baller machine, and 1 unit of grass chopper, so that the problems faced by the Program Partners in meeting the quota needs of their customers and increasing product shelf life can be resolved.